Habitat Analysis and Dietary Potential of Long Tailed Macaques (Macaca fascicularis, Raffles) in Tinjil Island - Nyoto Santoso (Department of Forest Resources Conservation and Ecotourism - IPB University, 1996)
Tinjil Island, coveringa total area of 600 ha, is a semi-natural captive breeding site for long-hailedmacaques.The increased populationof the macaques being bred, have shown the success of the breeding programme, thus there shouldbeanticipation of their dietary needs in thelongterm(porti0nand natural diets). Thedietary potential ofTinjil Island have not yet been adequately inventoried in terms of species, amounts and distributions. Therefore researchshould be conducted regarding the habitat's condition and potential diets of the Island.